Konsep dan Kedudukan Hak Kekayaan Intelektual dalam Hukum Islam - Miftakhul Huda (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
This research is a library research (library reseach) which seeks to answer the question of how the Copyright actually in the review of Islamic Sharia, whether Islam recognizes the existence of copyright, and how the principles of Islam in protecting copyright. Data obtained by reviewing literature literature. The research findings show that in the treasury of Islamic law copyright is known as Haq Al-Ibtikar, namely the right to a creation that was first made. Islam only recognizes and protects copyrighted works that are in line with the norms and values ​​contained in them. If the work is contrary to Islamic values, then it is not recognized as "copyrighted work" and there is no form of protection for this type of work. Protection of copyright in Islam has conditions that must be fulfilled so that a copyrighted work can be recognized as ownership rights to property, namely: Does not contain illicit elements in it, does not cause damage in the community, does not conflict with Islamic law in general. Copyright as an ownership right on a benefit will end when the owner does a contract (transaction), either a tabaru contract (social) or a tijary (trade).